Polydatin, natural precursor of resveratrol, promotes osteogenic differentiation of mesenchymal stem cells - Di Benedetto, Adriana; Posa, Francesca; De Maria, Salvatore; Ravagnan, Giampietro; Ballini, Andrea; Porro, Chiara; Trotta, Teresa; Grano, Maria; Muzio, Lorenzo Lo; Mori, Giorgio (International journal of medical sciences, 2018)
Bone loss and fractures are consequences of aging, diseases or traumas. Furthermore the increased number of aged people, due to the rise of life expectancy, needs more strategies to limit the bone loss and regenerate the lost tissue, ameliorating the life quality of patients. A great interest for non-pharmacological therapies based on natural compounds is emerging and focusing on the oligostilbene Polydatin, present in many kinds of fruits and vegetables, when resveratrol particularly in red wines. These molecules have been extensively studied due to their antioxidant and anti-inflammatory effects, showing more recently Resveratrol the ability to enhance osteogenic differentiation and bone formation. However, the clinical applications of Resveratrol are limited due to its low bioavailability and rapid metabolism, while its natural glycosilated precursor Polydatin shows better metabolic stability and major abundance in fresh fruits and vegetables. Nevertheless the role of Polydatin on osteogenic differentiation is still unexplored. Mesenchymal stem cells (MSCs) from dental tissues, such as dental bud stem cells (DBSCs), are able to differentiate toward osteogenic lineage: thus we investigated how Resveratrol and Polydatin influence the differentiation of DBSCs, eventually affecting bone formation. Our results showed that Polydatin increases MSCs osteogenic differentiation sharing similar properties with Resveratrol. These results encourage to deepen the effects of this molecule on bone health and its associated mechanisms of action, wishing for the future a successful use in bone loss prevention and therapy.
Gesehen am 03.12.2020